Bakunin the Creative Passion - Leier, Mark. (New York seven stories press, 2006)
The passion for destruction is a creative passion," wrote the anarchist Mikhail Bakunin in 1842. Since then, the popular image of anarchism has been one of violence and terror. But this picture is wildly misleading, and the media has done more to obscure anarchism than to explain it. Focusing on the street fighting and confrontations with police, mainstream commentators are unable to understand what anarchism is or why a philosophy with roots in the nineteenth century has resurfaced with such power at the dawn of the new millennium. To understand anarchism, it is necessary to go beyond the caricature presented by the media. In this new biography of Mikhail Bakunin, Mark Leier traces the life and ideas of anarchism's first major thinker, and in the process revealing the origins of the movement.
Includes index and bibliographies
Keywords: Biography